2014
DOI: 10.1097/hjh.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear association between pulse wave velocity and cognitive function

Abstract: Arterial stiffness was inversely associated with cognitive function in a nonlinear fashion, with individuals in the top decentile of cfPWV explaining the association. Results from linear regressions should thus be interpreted with caution because, even when statistical significance is reached, they can be explained by pronounced nonlinearity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…A priori power analysis based on previous experience of the same laboratory indicated that, previewing a difference around 1 between groups and a standard variation around 2 for each neuropsychological test, one‐hundred participants per group in equality for two proportion tests were sufficient to show effects with a power of 0.90 and a test level of 0.10 for β error and of 0.20 for α error. Linearity assumption was ascertained for each variable by the residuals method and normality assumption by the Kolmogorov–Smirnov one‐sample test .…”
Section: Methodsmentioning
confidence: 99%
“…A priori power analysis based on previous experience of the same laboratory indicated that, previewing a difference around 1 between groups and a standard variation around 2 for each neuropsychological test, one‐hundred participants per group in equality for two proportion tests were sufficient to show effects with a power of 0.90 and a test level of 0.10 for β error and of 0.20 for α error. Linearity assumption was ascertained for each variable by the residuals method and normality assumption by the Kolmogorov–Smirnov one‐sample test .…”
Section: Methodsmentioning
confidence: 99%
“…A possible explanation is that these individuals already have lower BP and therefore are more sensitive to BP drop, which might significantly reduce cerebral perfusion if the critical level is reached. Orthostatic hypotension has been associated with arterial stiffness [21] and earlier studies have implicated association between arterial stiffness and higher prevalence of cognitive dysfunction [22]. Consequently, reduced arterial compliance might mediate the increased risk of dementia seen in participants with lower BP and postural DBP decline.…”
Section: Discussionmentioning
confidence: 99%
“…This shows the close link between arterial stiffness, impaired glucose metabolism and overt type 2 diabetes -a different risk factor cluster than the more traditional cluster associated with atherosclerosis (hypertension, smoking, hyperlipidaemia). We have also found that c-f PWV is associated with a family history of cardiometabolic disease [3], impaired cognition [4], and is predictive of type 2 diabetes [5] and all-cause mortality, even adjusted for known risk factors/markers and family history of cardiometabolic disease (abstract, ARTERY 2017, Pisa, Italy). New drugs are being developed for vascular protection and the reduction of arterial stiffness.…”
Section: Biomedical and Biopharmaceutical Research J O R N A L D E I mentioning
confidence: 99%
“…According to an overall evaluation, 49-63% of all valve replacements with glutaraldehyde-treated BHVs [3] have been reported to be free from SVD 20 years after intervention. Otherwise the risk of structural failure is inversely related to the age of patients: it is higher in individuals <35 years of age in which up to 100% of BHVs fail within 5 years postsurgery whereas after 15 years 60-70% of older patients (>75 years) are still free of SVD [4]. In the vast majority of cases SVD is associated with leaflet calcium deposits even if in 19-25% of BHV implants reoperations occur in the absence of leaflet mineralization [5,6] (excluding nonintrinsic abnormalities, thrombosis and infections).…”
Section: Bioprosthetic Heart Valve Aging Deterioration and Agerelatedmentioning
confidence: 99%
See 1 more Smart Citation